Applications of nanofluids in solar energy: A review of recent advances. (February 2018) - Elsheikh, A.H.; Sharshir, S.W.; Mostafa, Mohamed E.; Essa, F.A.; Ahmed Ali, Mohamed Kamal
Abstract: Solar energy systems (SESs) are considered as one of the most important alternatives to conventional fossil fuels, due to its ability to convert solar energy directly into heat and electricity without any negative environmental impact such as greenhouse gas emissions. Utilizing nanofluid as a potential heat transfer fluid with superior thermophysical properties is an effective method to enhance the thermal performance of solar energy systems. The purpose of this review paper is the investigation of the recent advances in the nanofluids' applications in solar energy systems, i.e., solar collectors (SCs), photovoltaic/thermal (PV/T) systems, solar thermoelectric devices, solar water heaters, solar-geothermal combined cooling heating and power system (CCHP), evaporative cooling for greenhouses, and water desalination.